PENGARUH ENTERTAINMENT, IRRITATING DAN INFORMATIVENESS TERHADAP NILAI IKLAN DAN SIKAP TERHADAP PERIKLANAN DI WEB DI KALANGAN MAHASISWA DI JAKARTA BARAT - M. ARY BUDI YUWONO; FAUZIYAH HAYATI SYAHIR (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2002)
The growth of advertising on the World Wide Web requires research on users' general perceptions since these attitudes toward individual advertisements. This article presents results of a survey among university students focusing on the perceived value of Web Advertising in the general media. Both the hypothesized model of advertising value and its role as an antecedent of overall audience attitudes are confirmed.